SISTEM PERBENIHAN KEDELAI MELALUI SISTEM JABALSIM DI SENTRA PRODUKSI KEDELAI JAWA TENGAH - Eny Hari Widowati; Alfina Handayani; Imam Sutrisno (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2014)
Soybean is the third important food crop after rice and maize. Every year, the more number of populations in Central Java, the more soybean consumption. However, the supply of soybean is not fulfill the needs because the soybean productivity is still low. Low soybean productivity is affected by the unqualified seed.The research was conducted by quantitative descriptive approach for 3 months in Grobogan and Wonogiri Regency. The respondents are farmers, traders and airy companion. The research results showed that the soybeans cropping pattern in Grobogan and Wonogiri held in rainfed on the first and second rainy season from October to March. In the first and second drought season in June to September, soybean is planted in the paddy field. The soybean seed needs were 40 kg/ha in Grobogan and 70 kg/ha in Wonogiri. In a year, soybean seed needs were 2.76114 million pounds. The most crucial seed needs in May, September and October amounted to 1,706,139 kg. Soybean seed system was obtained by storage in the form of dry stover to process from consumption soybean product by sorting in Wonogiri, also to process the cultivated soybean production that using labeled seeds in Grobogan.Recommendation: Local agricultural agencies should be facilitated seed lebelled for supply of seeds that is coached by Bakorluh.